2009
DOI: 10.1111/j.1749-6632.2009.04424.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological Mechanisms of Placebo Responses

Abstract: Expectations, positive or negative, are modulating factors influencing behavior. They are also thought to underlie placebo effects, potentially impacting perceptions and biological processes. We used sustained pain as a model to determine the neural mechanisms underlying placebo-induced analgesia and affective changes in healthy humans. Subjects were informed that they could receive either an active agent or an inactive compound, similar to routine clinical trials. Using PET and the mu-opioid selective radiotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
149
1
11

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(168 citation statements)
references
References 78 publications
(89 reference statements)
7
149
1
11
Order By: Relevance
“…Generally, this tends to increase treatment effects compared to blinded studies (Schulz et al, 1995;Day and Altman, 2000), and is especially problematic in these studies where the cases were self-reported EHS patients. Studies have shown that placebo or nocebo effects can modulate perception and biological processes inducing measurable physiological changes (Enck et al, 2008;Zubieta and Stohler, 2009), and indeed changes in blood glucose levels in these studies can alternatively plausibly be ascribed to expectation and anxiety (Surwit et al, 1992;Surwit and Schneider, 1993;Park et al, 2008) rather than to the reduction in exposure. Furthermore, both exposure and biological response are self reported and have been measured at random moments throughout the day.…”
Section: Health Effectsmentioning
confidence: 79%
“…Generally, this tends to increase treatment effects compared to blinded studies (Schulz et al, 1995;Day and Altman, 2000), and is especially problematic in these studies where the cases were self-reported EHS patients. Studies have shown that placebo or nocebo effects can modulate perception and biological processes inducing measurable physiological changes (Enck et al, 2008;Zubieta and Stohler, 2009), and indeed changes in blood glucose levels in these studies can alternatively plausibly be ascribed to expectation and anxiety (Surwit et al, 1992;Surwit and Schneider, 1993;Park et al, 2008) rather than to the reduction in exposure. Furthermore, both exposure and biological response are self reported and have been measured at random moments throughout the day.…”
Section: Health Effectsmentioning
confidence: 79%
“…Obvious candidates include the ventral striatum, the amygdala, the insular and anterior cingular cortices and possibly other structures where the opioid system interacts with dopaminergic neurotransmission (e.g. Zubieta & Stohler, 2009). The interactions may operate via influences on valence processing and/ or more directly on (working-) memory-related pathways Several potential confounders were considered in this study, including (1) stress, (2) drug-induced emotional blurring and (3) unspecific drug-related cognitive effects potentially affecting attention.…”
Section: Discussionmentioning
confidence: 99%
“…Within the field of placebo research, endogenous opioids were the first neurobiological substrates consistently enlisted as a physiological mediator of the placebo effect -when the administration of the opioid-antagonist Naloxone was shown to reduce placebo-mediated analgesia (Levine, Gordon, and Fields, 1978). Since then, placebo research has expanded enormously and opioids continue to play a prominent role (Price, Finniss, and Benedetti, 2008;Zubieta and Stohler, 2009). For example, brain-imaging studies have begun to specify the role of opioids in placebo processes by localizing placebo-induced functional changes in opioid-signalling in the brain (Zubieta, Bueller, Jackson, Scott, Xu, Koeppe, Nichols, and Stohler, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Dopamine release within the nucleus accumbens occurs following alleviation of ongoing pain, or the expectation of pain relief [30]. However, direct evidence for modulation of dopamine in the nucleus accumbens by aversive stimuli has been demonstrated.…”
Section: Interplay Between Reward and Painmentioning
confidence: 99%